Biological Durability of Wood–Polymer Composites—The Role of Moisture and Aging - Buschalsky, Andreas; Brischke, Christian; Klein, Kim Christian; Kilian, Thomas; Militz, Holger (Materials, 2022)
Knowledge about the resistance of wood–polymer composites (WPCs) to biological attack is of high importance for purpose-oriented use in outdoor applications. To gain this knowledge, uniform test methods are essential. EN 15534-1 (2018) provides a general framework, including the recommendation of applying a pre-weathering procedure before the biological laboratory tests. However, the procedure’s manner is not specified, and its necessity assumes that a durability test without such pre-weathering will not produce the structural changes that occur during outdoor use. To verify this assumption, this study examined the influence of natural, ground-level pre-weathering on the material properties of different WPC variants, which were tested at intervals of six months in four durability tests under laboratory conditions in accordance with EN 15534-1 (2018). Weathering factors were calculated from determined characteristic values such as mass loss, and loss in moduli of elasticity (MOE) and rupture (MOR). The weathering factors based on mechanical properties tended to decrease with increasing weathering duration. The expected negative influence of pre-weathering on these material properties was thus not confirmed. The weathering factors based on mass loss were subject to high variation. No significant effect of pre-weathering on mass loss due to fungal attack became evident. Overall, the necessity of a pre-weathering step in biological durability tests shall be questioned based on the presented results.